The Comparability of National Income Statistics of English-Speaking Countries - Abraham, William I. (The Review of Economics and Statistics, 1948)
THIS paper aims at clarifying existing similarities and differences in the field of national income statistics in six English-speaking countries.' The discussion proceeds in three stages. First, the general lines of development and the present status of national income research in the several countries, as reflected in their latest official publications, are described. The definition of national income employed in each country is then examined in detail, and particular attention is focused on areas of disagreement. Finally, the estimates of national income based on the respective national definitions are adjusted to show national income according to a common definition. In the last year, four new official national income publications have been issued in Engglish-speaking countries. These publications not only present revised estimates of national income and related aggregates but, more important for our purpose, bring to light the recent changes in definitions and methodology adopted by national statistical authorities. The most comprehensive of such publications is National Income and Product Statistics of the United States, I929-46, issued as a Supplement to the Survey of Current Business, July I947. This publication presents revisions of the basic aggregates, largely the result of important changes in the treatment of certain items, and at the same time integrates the entire body of national income statistics within a framework of social or national accounts 2 covering the major sectors of the economy. The other publications make a less dramatic break with the past, and the revisions shown do not stem primarily from changes in definition. National Income and Expenditure of the United Kingdom, I938 to I946, prepared in the Central Statistical Office, differs from the preceding White Paper on the subject chiefly in that a system of social accounts for the years I938 and I946 is appended. The Australian paper, National Income and Expenditure, I946-47, also differs from its predecessor mainly in that a simplified system of social accounts for two years is shown. The Canadian publication of the Dominion Bureau of Statistics, National Accounts, Income and Expenditure, I938-I946, which presents some new breakdowns, notably of personal expenditure, reveals no striking departures from preceding publications, and must be studied in connection with its forerunner of a year ago which contained much fuller notes and explanations.3 Two other English-speaking countries which can conveniently be dealt with here are Eire and New Zealand. As of this moment, no successor to the Eire publication, National Income and Expenditure, I938-I944, has appeared. New Zealand still does not publish estimates of national income but makes use of private a concept related to private income as used in most other countries.4 While the year to year variations in aggregate private income probably afford a reasonable guide to changes in national income, aggregate private income undoubtedly understates national income. ' United States, Canada, United Kingdom, Eire, Australia, and New Zealand. For a broader survey and analysis covering all countries, together with an account of the national income work being carried on in the Statistical Office of the United Nations, see The Comparability of National Income Statistics (mimeographed) by Dr. J. B. D. Derksen, a paper presented at the International Statistical Conferences held in Washington, D. C. in September, I947. The present author wishes to acknowledge his indebtedness to the National Income Section of the Statistical Office, and in particular to Dr. Derksen. The views expressed in this paper are, of course, not to be construed as binding on the Statistical Office. 2 Editorial note. For a discussion of this publication, see pp. I5I-I97, above. 3 Since the above was written, preliminary figures for I947 have been made public in a two-page pamphlet National Accounts, Income and Expenditure, Preliminary,